2021
DOI: 10.1126/science.abh2444
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells expand potency and alter tissue fitness by accumulating diverse epigenetic memories

Abstract: Stem cells remember Tissue stem cells sense their surroundings, and this perception influences subsequent fate and function. Gonzales et al . observed that stem cells accumulate epigenetic memories of diverse environmental events (see the Perspective by Hoste). By wounding skin and monitoring the temporal steps involved in mobilizing stem cells of the hair follicle to repair the epidermis, the authors found that stem cells bear memories of their original niche, mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 61 publications
3
71
1
Order By: Relevance
“…Although stem cell mechanical memory and cellular reprogramming had previously been shown ( 5, 20, 29 ), our findings reveal that such memory can be encoded into the ECM. In stem cells, cardiac cells and breast cancer cells, mechanical priming can result in chromatin remodeling ( 3032 ), causing epigenetic modifications and potentially mechanical memory.…”
Section: Discussioncontrasting
confidence: 47%
“…Although stem cell mechanical memory and cellular reprogramming had previously been shown ( 5, 20, 29 ), our findings reveal that such memory can be encoded into the ECM. In stem cells, cardiac cells and breast cancer cells, mechanical priming can result in chromatin remodeling ( 3032 ), causing epigenetic modifications and potentially mechanical memory.…”
Section: Discussioncontrasting
confidence: 47%
“…First, cells cycling among states impacts mutation and epigenetic alterations and their penetrance, and NWD1 decreased Lgr5 hi cell mutation accumulation while increasing mutational burden from the expanded Bmi1+ cell population (Li et al, 2019a; Li et al, 2019b). Second, epigenetic “history” of a cell dictates its future course and responses to signals (Gonzales et al, 2021). Third, impact of onco- and tumor suppressor genes and key regulators are always context dependent, with major differences in the role and regulation of such genes among tissues and lineages in both normal functioning and as drivers of disease.…”
Section: Discussionmentioning
confidence: 99%
“…While the capacity of cells in other organs to retain memory of previous insults has been previously established (Kisseleva et al , 2012; Naik et al , 2017; Gonzales et al , 2021; Larsen et al , 2021), whether the lung mesenchyme possesses the capacity to retain memory has remained relatively unexplored. Our findings that the lung mesenchyme retains fibrotic-relevant memory following fibrogenic injury resolution demonstrates a new and unappreciated role of these cells in the amplified response to repetitive injury.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly a decade ago it was shown that a portion of hepatic stellate cells that are activated by liver injury undergo deactivation after successful resolution of fibrotic injury but retain an altered state that accelerates subsequent in vitro activation (Kisseleva et al , 2012). More recently, epithelial stem cells of the skin have been shown to retain epigenetic memory of prior tissue injury and inflammation (Naik et al , 2017; Gonzales et al , 2021; Larsen et al , 2021). In both cases, such memory is thought to provide an evolutionary advantage and protective role by accelerating wound repair following a second tissue insult.…”
Section: Introductionmentioning
confidence: 99%